2019
DOI: 10.3390/pathogens8040185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Avian Gyrovirus 2 Variant-Related Gyrovirus Detected in Farmed King Ratsnake (Elaphe carinata): The First Report from China

Abstract: Avian gyrovirus 2 (AGV2), which is similar to chicken infectious anemia virus, is a new member of the genus Gyrovirus. AGV2 has been detected not only in chicken but also in human tissues and feces. This study analyzed 91 samples (8 from liver tissue and 83 from fecal samples) collected from king ratsnakes (Elaphe carinata) from 7 separate farms in Hubei and Henan, China, for AGV2 DNA using PCR. The results demonstrated a low positive rate of AGV2 (6.59%, 6/91) in the snakes, and all the positive samples were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Most GyVg1 strains are detected mainly in chickens, but they have been also detected in various hosts such as ferrets, snakes, and dogs, suggesting possible cross-species transmission [ 7 , 11 , 12 , 13 , 14 , 16 ]. Additionally, GyVg1 has been detected in the blood of healthy humans, transplant recipients and HIV-positive patients [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most GyVg1 strains are detected mainly in chickens, but they have been also detected in various hosts such as ferrets, snakes, and dogs, suggesting possible cross-species transmission [ 7 , 11 , 12 , 13 , 14 , 16 ]. Additionally, GyVg1 has been detected in the blood of healthy humans, transplant recipients and HIV-positive patients [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sauvage et al [ 8 ] identified human gyrovirus, which shares 96% nucleotide identity with GyVg1, from the skin swab of a healthy individual, indicating that GyVg1 might also infect humans. Subsequently, GyVg1 was detected in human blood samples [ 9 , 10 ], human feces [ 11 , 12 ], ferret feces [ 13 ], snakes [ 14 ], ticks [ 15 ], and dogs [ 16 ], suggesting that the virus can infect a broad range of animals.…”
Section: Introductionmentioning
confidence: 99%
“…As a snake with a long history of captive breeding, the reproduction and the viruses carried by the king ratsnake have been well studied [ 10 , 11 ] . However, there is insufficient research on its immune resistance and a general lack of genomic resources.…”
Section: Main Contentmentioning
confidence: 99%
“…Since 2011, a series of circovirus sequences similar to CAV (HGyV/AGV2, GyV3 through GyV13) have been reported ( Sauvage et al, 2011 ; Chu et al, 2012 ; Niu et al, 2019 ; Feher et al, 2022 ; Ji et al, 2022 ). These viruses have been identified in birds (chicken, northern fulmar, crested screamer, ashy storm petrel, ferruginous-backed antbird, white-plumed antbird, grey teal, pigeon, Pekin duck), mammals (human, cat, dog, ferret, mice) and reptiles (king rat snake) ( Feher et al, 2014 ; Truchado et al, 2019 ; Wu et al, 2019 ; Ji et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%